EDP auditing: accounting controls and problems in an EDP (Electronic Data Processing) environment / Norhayati Z. Abidin - Z. Abidin, Norhayati (1990)
The objective of this project paper is to study in general what are the accounting controls in the computerised environment and to highlight any problems faced upon the absence of these controls.